The Hybridization of Street Offending in the Netherlands. (29th December 2020) - Roks, Robert A; Leukfeldt, E Rutger; Densley, James A
Abstract: Based on the results of two research projects from the Netherlands, this paper explores how street-oriented persons adapt and use digital technologies by focussing on the changing commission of instrumental, economically motivated, street crime. Our findings show how social media are used by street offenders to facilitate or improve parts of the crime script of already existing criminal activities but also how street offenders are engaging in criminal activities not typically associated with the street, like phishing and fraud. Taken together, this paper documents how technology has permeated street life and contributed to the 'hybridization' of street offending in the Netherlands—i.e. offending that takes place in person and online, often at the same time.